Postavení fluorochinolonů v antimikrobní terapii a profylaxi v chirurgii - Vyhnánek, F; Lochmann, O (Rozhledy v chirurgii, 1995)
The authors evaluate, based on laboratory and clinical experiments, the importance of quinolones in the antimicrobial prophylaxis and therapy in surgery. In the laboratory investigations they assessed the present state of resistance of some Gram-negative and Gram-positive bacteria to fluoroquinolones-pefloxacine, ofloxacine and ciprofloxacine. In the clinical part the authors made a comparative study of pefloxacine and a cephalosporin of the third generation, ceftazidime, in the treatment of nosocomial postoperative and posttraumatic inflammatory affestions of the lower airways in 20 patients in both groups. The patients were hospitalized at the intensive care unit in 1993-1994. The action of the two chemotherapeutic agents was comparable, in 18 patients of both groups the infections disappeared and regression of the inflammatory pulmonary affection was recorded.
Keywords: Pneumonia, Bacterial; rány a poranění; antiinfekční látky; ceftazidim; 4-Quinolones; antibiotická rezistence; Quinolones; Anti-Infective Agents; Middle Aged; mužské pohlaví; bakteriální pneumonie; Cross Infection; 4-chinolony; pooperační komplikace; Postoperative Complications; Pefloxacin; chinolony; ženské pohlaví; fluorochinolony; Humans; Premedication; Fluoroquinolones; lidé středního věku; Wounds and Injuries; infekce spojené se zdravotní péčí; Drug Resistance, Microbial; premedikace; Female; pefloxacin; lidé; Male; Ceftazidime